Gender differences in cardiac left ventricular mass and function: clinical and experimental observations - Escudero, Eduardo Manuel (2014)
Background: The aim of this study was to evaluate gender-associated impact on left ventricular mass (LVM) and on left ventricular function (LVF) in humans and rats with aging. Methods: Myocyte area and collagen volume fraction (CVF) were studied in rats. LVM and LVF were evaluated in animals and humans by echocardiography and LVM index (LVMI) was obtained. Results: LVMI, myocyte area and CVF were similar in males and females of 1-month-old rats. LVMI in children was similar in both genders. In contrast, in 6-month-old rats (5 males and 5 females), LVMI (17.7 ± 0.7 mg/mm vs. 10.1 ± 0.2 mg/mm; p < 0.01), and myocyte area (4572.5 ± 72.6 μm2 vs. 3293.85 ± 57.8 μm2, p < 0.01) were higher in male animals without differences in CVF. Men (n = 25) exhibited greater LVMI than women (n = 25) (77.4 ± 3.2 g/m2 vs. 63.3 ± 1.8 g/m2, p < 0.01), whereas the LVF was higher in women (105.9 ± 2.9% vs. 95.3 ± 3.5%, p < 0.01). Conclusions: There is a clear gender-associated impact on LVM with aging in humans and rats. Similar CVF and LVF associated to greater myocyte size and LVM in male rats suggest a process of physiological response. However, the increase in cardiac mass without an associated improved cardiac function in men in comparison to women could likely represent a potential disadvantage in the adaptive response during growth.